Sposoby ujmowania edukacji ekologicznej - Agnieszka Bernadkiewicz (Studia Ecologiae et Bioethicae)
Recently, relation between human being and nature is mainly that environmental resources are gained by people to assurance themselves worthy living conditions. People’s actions are often not very well motivated, leading to serious consequences such as degradation of environmental components. The way of making use of biosphere components are undoubtedly depend on degree of ecological awareness and on people’s responsibility for environment. A creation of pro-ecological attitudes is one of main goals of ecological education. This article shows the ways of understanding ecological education, the areas of its interest, its essence, and the most important trends and values in the contemporary world.